The association between digit ratio (2D:4D) and overweight or obesity among Chinese children and adolescents: A cross-sectional study - Wu, Lu (Study of serum leptin in well differentiated thyroid carcinoma: Correlation with patient and tumor characteristics, 2019)
The aim of this study was to analyze the relationship between 2D:4D and childhood overweight or obesity, which might indirectly show the role of prenatal hormone in childhood overweight or obesity.